Heavy quark symmetry behind b → c semileptonic sum rule - Motoi Endo; Syuhei Iguro; Satoshi Mishima; Ryoutaro Watanabe (Journal of High Energy Physics)
Abstract Lepton flavor universality violations in semileptonic b → c transitions have garnered attention over a decade. For $${R}_{H_{c}}={\text{BR}}\left(H_{b}→ H_{c}τ {\overline{ν }}_{τ }\right)/{\text{BR}}\left(H_{b}→ H_{c}{\ell}{\overline{ν }}_{{\ell}}\right)$$ with ℓ being e, μ, a sum rule among R D , $${R}_{D^{*}}$$ and R Λc was proposed to check consistency in the experimental results independently of new physics models. We revisit this relation from the perspective of the heavy quark symmetry. We derive a sum rule holding exactly in the heavy quark limit and clarify how model-dependent corrections are introduced in a realistic situation.